Antifungal activity of essential oil from Mentha spicata L. and Mentha pulegium L. growing wild in Sardinia island (Italy). Issue 6 (19th March 2021) - Piras, A.; Porcedda, S.; Falconieri, D.; Maxia, A.; Gonçalves, Mj.; Cavaleiro, C.; Salgueiro, L.
Abstract: This study aims to evaluate the antifungal activity of Mentha spicata L. and Mentha pulegium L. from Sardinia and to assess their efficacy on virulence factors for Candida albicans, particularly on the inhibition of the germ tube formation. The major compounds of the essential oils were carvone (62.9%) for M. spicata and pulegone (86.2%) for M. pulegium . The essential oil from M. spicata showed a more preeminent effect against Cryptococcus neoformans and the dermatophytes Trichophyton rubrum and T. verrucosum (0.32 μL/mL). Both oils were very effective in inhibiting C. albicans germ tube formation, at doses well below their MIC (0.16 μL/mL). Graphical Abstract: